Juridical-theological definition of the consecrated life by profession of the evangelical counsels - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2017)
The term consecrated life appeared quite recently. Though it is commonly used, and yet – as it seems – it is not understand to the full extend even by the very persons to whom it refers. That’s because not many of them read the John Paul’s II Canonical Law Code of 1983, where there is given a full definition of the consecrated life. The term is usually explained as the life particularly sacrificed (consecrated) to God. At the same time sacrament of baptism - called also by the term of baptismal consecration - already dedicates the life of each baptized to God, so it becomes a true consecrated life. Likewise a priest by reception of the consecration sacrament simultaneously sacrifices himself to God. What kind of consecration then we are talking about in the case of so called consecrated persons? When it takes place, and what so much distinguishes the consecrated persons, that they create separate class in the Church, though it is not a hierarchic one? The answers for such questions are given in the article, which analyses the Code’s definition of the consecrated life, and its forms existing in the Catholic Church.